PERBANDINGAN HASIL BELAJAR IPA SISWA MENGGUNAKAN MODEL PEMBELAJARAN TS-TS DENGAN TPS KELAS VIII MTsN GOWA - Ikram Ikram; Andi Maulana; Saprin Saprin (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
The aim of this research is to know the comparison of students’ IPA learning outcomes by using TS-TS and TPS type of cooperative learning model in the VIII class of MTs Negeri Gowa. The kind of this research was quasi experimental with the nonequivalent posttest-only control group design. The population of this research was the second grade students of MTs Negeri Gowa which have two classes. Then, the researcher decided the sample with saturation sampling. The research instrument was using test of learning outcomes after giving treatment. The analysis techniques were using descriptive statistical analysis and inferential statistical analysis. The result of descriptive analysis showed that the average of students’ learning outcomes with cooperative model by using TS-TS was 12,43 at the high category with 50% percentage while the cooperative model by using TPS type also at the high category with 46,875% with the average score at 14,25. Then, the result of inferential analysis showed that there were the significant difference between students’ IPA learning outcomes after using TS-TS and TPS type of cooperative learning model with the result of calculation score in thitung>ttabel (2,6033>1,67) which means H2 was rejected. Based on the result of research, it could be known that TS-TS and TPS type of cooperative learning model can increase students’ learning outcomes at VIII class of MTsN Gowa.